2012
DOI: 10.1038/bjc.2012.479
|View full text |Cite
|
Sign up to set email alerts
|

EGFR and K-ras gene mutation status in squamous cell anal carcinoma: a role for concurrent radiation and EGFR inhibitors?

Abstract: Background:There is a growing appreciation for radio-sensitiser use in multi-modal cancer treatment models. Squamous cell anal carcinoma (SCAC) is a rare gastrointestinal tumour traditionally treated with concurrent chemotherapy and radiation. Cetuximab, an epidermal growth factor receptor (EGFR) inhibitor, has demonstrated significant efficacy when combined with radiation in squamous cell carcinoma of the head and neck (SccH&N). We wanted to assess EGFR and Kirsten-ras (K-ras) status in SCAC to see whether it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 32 publications
6
33
0
2
Order By: Relevance
“…4 EGFR is often overexpressed and/or abnormally activated in almost all squamous cell carcinomas (SCCs), including anal carcinomas (in up to 90%). 5 Cetuximab (Erbitux; Merck KgaA, Darmstadt, Germany) is an immunoglobulin G1 monoclonal antibody that specifically targets EGFR, competitively inhibiting ligand binding and ligand-dependent downstream signaling. 6 Phase 1 clinical trials demonstrated the safety of cetuximab combined with CP 7 and cetuximab combined with radiation therapy 8 in SCCs other than anal carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…4 EGFR is often overexpressed and/or abnormally activated in almost all squamous cell carcinomas (SCCs), including anal carcinomas (in up to 90%). 5 Cetuximab (Erbitux; Merck KgaA, Darmstadt, Germany) is an immunoglobulin G1 monoclonal antibody that specifically targets EGFR, competitively inhibiting ligand binding and ligand-dependent downstream signaling. 6 Phase 1 clinical trials demonstrated the safety of cetuximab combined with CP 7 and cetuximab combined with radiation therapy 8 in SCCs other than anal carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies evaluated the determination of K-RAS mutation in 146 patients in total. None of the assessments showed the presence of the mutated K-RAS form [25,35]. A larger study evaluated 193 biopsies, demonstrating the K-RAS mutation in only 3 cases [36].…”
Section: Discussionmentioning
confidence: 99%
“…EGFR-TKIs (EGFR-tyrosine kinase inhibitors), erlotinib and gefitinib are the other proficient drugs in clinical trials with antitumor activity (Table 2). Recent studies on squamous cell anal carcinoma (SCAC) showed significantly less prevalence of EGFR and K-ras mutations in head and neck cancer [116] with cetuximab showing appreciable anticancer effect when administered in synergy with radiation.…”
Section: Targeting Oncogenic Rasmentioning
confidence: 99%